Ultrasound-assisted Synthesis of 6-substituted indolo[2,3-b]quinolines: their Evaluation as Potential Cytotoxic Agents - Marepu, Nagaraju; Gosi, Mahesh; Vedula, Santhoshi S.; Yeturu, Sunandamma; Pal, Manojit (Mini Reviews in Medicinal Chemistry, 2019)
Background: The indolo[2,3-b]quinoline framework is often found in various natural products displaying a range of pharmacological activities. This is an attractive template for the design and discovery of potential drugs especially for the identification of new anticancer agents. Methods: The synthesis of 6-substituted indolo[2,3-b]quinolones was undertaken and carried out using a ultrasound assisted method involving two sequential C-N bond forming reactions between 3-(2- bromophenyl)-2-chloroquinoline and amines in a single pot in the presence of Pd(OAc)2 and a ligand (S)-BINAP. All the synthesized compounds were tested in vitro against two cancer cell lines e.g. MCF7 and HepG2 along with non-cancerous HEK293 cell lines. Results: Two of these compounds showed promising and selective growth inhibition of MCF7 cell lines and one induced significant apoptosis in cancer (MCF7) cells. Conclusion: Compounds based on indolo[2,3-b]quinolone framework may be useful for the identification of new cytotoxic agents thereby potential cure for breast cancer.
Keywords: cancer cells